Lean Manufacturing Readiness Amongst Smes In Bauchi Region, Nigeria: An Analysis Of The Socio-technical Environmental Framework - Inuwa, Mohammed (2022)
Most SMEs have experienced difficulties during Lean deployment due to a lack of assessment of organizational readiness to change. Similarly, there is shortage of Lean manufacturing buy-in and lack of implementation within manufacturing SMEs in Nigeria. Consequently, the study applies socio-technical systems and Lewin's change theories to evaluate Lean readiness within manufacturing SMEs. Analysis of data was based on 300 responses obtained through questionnaires distributed to SME managers within the manufacturing sector in Nigeria. The hypothesis was tested using the partial least square- structural equation modelling (PLS-SEM) 3.3 version. The findings reveal that organizational culture is positive and significantly related to supplier and customer relations. Leadership/top management also has a positive and significant relationship with customer relations. On the contrary, leadership/top management does not predict supplier relations. Also, employee relations have an insignificant relationship with suppliers and customers relations. It was found that the relationship between supplier and customer relations was positive and significant on organizational readiness for change (change efficacy and change commitment). Supplier relations significantly mediate the relationship between organizational culture and change commitment. However, supplier relations do not significantly mediate organizational culture and change efficacy.